Working Capital Turnover, Liquidity, Solvency and Firm Size Effect on Profitability - Akhmad Darmawan; Hanif Dwi Cahyo; Fatmah Bagis; Dwi Vina Rahmawati (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2022)
Abstract-The purpose of this study was to determine the effect of working capital turnover, liquidity, solvency and firm size on profitability. The research data used is secondary data. The total population used is 30 food and beverage companies for the 2017-2020 period. This sampling technique uses a purposive sampling technique with a research sample of 18 companies and a data sample of 65 data. Based on the multiple regression analysis tool, previously the data was tested using the classical assumption test and it is known that working capital turnover has no significant effect on profitability, liquidity has no significant affect on profitability, solvency has a significant effect on profitability and firm size has no significant effect on profitability. Keywords: Working capital turnover, Liquidity, Solvency, Firm size and Profitability